2015
DOI: 10.1155/2015/540828
|View full text |Cite
|
Sign up to set email alerts
|

Italian Validation of the 12-Item Multiple Sclerosis Walking Scale

Abstract: Objective. Gait impairment is commonly in people with multiple sclerosis (MS). The 12-item MS walking scale (MSWS-12) assesses patients' measurement of walking quality. The aim of this study was to cross-culturally adapt and validate the MSWS-12 for the Italian population with MS. Methods. Six MS out-patient clinics across Italy enrolled subjects between June 2013 and December 2013. Construct validity of MSWS-12 was determined by examining correlations with the Italian version of the EDSS, the timed 25-foot wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…6,23 Previously reported Cronbach’s alpha also confirms a high internal consistency of the items. 6,9,10,2325 Over different language versions similar results are found. To investigate whether there are no cultural and language differences between versions, DIF analyses could be performed using “language” as group variable.…”
Section: Discussionsupporting
confidence: 76%
“…6,23 Previously reported Cronbach’s alpha also confirms a high internal consistency of the items. 6,9,10,2325 Over different language versions similar results are found. To investigate whether there are no cultural and language differences between versions, DIF analyses could be performed using “language” as group variable.…”
Section: Discussionsupporting
confidence: 76%
“…The questions focus on the self-perceived impact of MS on 12 dailylife locomotor activities in the last 2 weeks. The transformed total score is between 0 and 100, with higher scores indicating higher perceived walking difficulties [13,27].…”
Section: Clinical and Instrumented Assessmentmentioning
confidence: 99%
“…Among the demographic factors, age and disease duration in the patients with MS were not correlated with the MSWS-12 scores, which contrasts with the findings of a previous study. 12 This discrepancy could be related to either the small number of patients included in our study or, considering that most of the patients showed relatively low EDSS scores that were not correlated with age or disease duration in our MS cohort, to specific characteristics of our cohort. These results were similar in the patients with NMOSD.…”
Section: Jcnmentioning
confidence: 76%
“…7,8 The 12-item Multiple Sclerosis Walking Scale (MSWS-12) is a commonly adopted patient-reported outcome measure used to assess the extent to which MS impacts the walking ability, 9 and it is currently the only qualitative, patient-based test that specifically measures walking disabilities. The MSWS-12 is easy to administer in a clinical setting for measuring walking difficulties in daily life, and it has been translated into various languages and validated as a useful tool in MS. [10][11][12][13][14] However, the MSWS-12 has not been validated for Korean MS patients, and moreover its applicability has not been evaluated for patients with NMOSD. The aim of this study was to adapt and validate a Korean version of the MSWS-12 for the Korean population with MS and NMOSD.…”
Section: Jcnmentioning
confidence: 99%